Therapeutic potential of Ganoderma lucidum polysaccharide peptide in Doxorubicin-induced nephropathy: modulation of renin-angiotensin system and proteinuria - Fang, Hui; Lin, Dongmei; Li, Xinxuan; Wang, Lianfu; Yang, Teng (Frontiers in Pharmacology, 2023)
In the Doxorubicin (DOX)-induced nephropathy model, proteinuria is a manifestation of progressive kidney injury. The pathophysiology of renal illness is heavily influenced by the renin-angiotensin system (RAS). To reduce renal RAS activation and proteinuria caused by DOX, this study evaluated the effectiveness of Ganoderma lucidum polysaccharide peptide (GL-PP), a new glycopeptide produced from Ganoderma lucidum grown on grass. Three groups of BALB/c male mice were created: control, DOX, and DOX + GL-PP. GL-PP (100 mg/kg) was administered to mice by intraperitoneal injection for 4 weeks following a single intravenous injection of DOX (10 mg/kg via the tail vein). After 4 weeks, full-length and soluble pro(renin) receptor (fPRR/sPRR) overexpression in DOX mouse kidneys, which is crucial for the RAS pathway, was dramatically inhibited by GL-PP therapy. Additionally, GL-PP successfully reduced elevation of urinary renin activity and angiotensin II levels, supporting the idea that GL-PP inhibits RAS activation. Moreover, GL-PP showed a considerable downregulation of nicotinamide adenine nucleotide phosphate oxidase 4 (NOX4) expression and a decrease in hydrogen peroxide (H2O2) levels. GL-PP treatment effectively reduced glomerular and tubular injury induced by DOX, as evidenced by decreased proteinuria, podocyte damage, inflammation, oxidative stress, apoptosis, and fibrosis. GL-PP inhibits intrarenal PRR/sPRR-RAS activation and upregulation of NOX4 and H2O2, suggesting potential therapeutic approaches against DOX-induced nephropathy.